Narwhal on a sunny night - Osborne, Mary Pope; Ford, AG (New York : Random House, 2020)
The magic tree house whisks Jack and Annie away to Greenland where they discover they've traveled back in time to meet Lief Erikson.
3.0
K-3
440L
Keywords: Leiv Eiriksson, -- -approximately 1020 -- Juvenile fiction; Time travel -- Juvenile fiction; Vikings -- Juvenile fiction; Narwhal -- Juvenile fiction; Magic -- Juvenile fiction; Tree houses -- Juvenile fiction; Greenland -- History -- Juvenile fiction; Leiv Eiriksson, -- -approximately 1020 -- Fiction; Time travel -- Fiction; Vikings -- Fiction; Narwhal -- Fiction; Magic -- Fiction; Tree houses -- Fiction; Greenland -- History -- Fiction; Time-travel fiction